Tomás de Aquino, la voluntad y la Ética a Nicómaco - David M. Gallagher (Tópicos, 2013)
This article points to several ethical themes in which Thomas Aquinas' analysis employs the notion of will while Aristotle's does not. It argues that Aquinas' explanations are more complete precisely because he introduces the will into the discussion. This introduction of the will represents a greater emphasis on the freedom of moral acts.